A MPCC-Based Variable Sampling Time Interleaving Method for a Two-Phase Totem-Pole Bridgeless Boost PFC Converter - Hyun-Gyu Koh; Hyeon-Joon Ko; Yeong-Jun Choi (IEEE Access)
This paper proposes a Model Predictive Current Control (MPCC) based variable sampling time interleaving method to improve the current shaping ability, power conversion efficiency, power density and current ripple reduction of a two-phase totem pole bridgeless boost power factor correction (PFC) converter. The proposed method is based on the Finite Control Set-Model Predictive Control (FCS-MPC) technique, which has the advantage of easily including nonlinear constraints among Model Predictive Control (MPC). However, since ON/OFF of the switch is determined through model-based cost function comparison, the switching frequency is variable and a separate modulator is not used. As a result, it is difficult to apply an interleaving method using a phase shift of a Pulse Width Modulation (PWM) carrier wave in each phase using an existing inductor and switch in two phases. Accordingly, in order to reduce the current ripple, a method of making the switching states of the two phases independent by varying the MPCC sampling time of one phase was proposed.